FREQUENCY OF OCCURRENCE OF PHONEMES IN HINDI - Sreedevi N; Irfana M; Anu Rose Paulson (Master Program in Linguistics, Diponegoro University, 2022)
Hindi, an Indo-Aryan language is the national language of India and the state language of various North Indian states of India such as Madhya Pradesh, Delhi, Uttar Pradesh etc. Statistics on the phonemes of a language provides useful information in the field of speech language pathology, audiology, linguistics and communication engineering. The data can be effectively used for the assessment and selection of target phonemes for treatment of various communication disorders, develop phonetically balanced word lists for audiological testing, and teach foreign language. It also provides valuable information to device text to speech systems and automatic speech recognition systems. The earlier data on frequently occurring phonemes in numerous Indian languages were derived from written sources. However, information from spoken language may be of more significance compared to written language. The aim of the present study was to determine the frequently occurring phonemes in spoken Hindi. Participants were native speakers of Hindi in the age range of 20 to 70 years. Eighteen group conversation samples were recorded. The samples were transcribed using IPA transcription. Systematic Analysis of Language Transcripts (SALT) software was used to analyze the samples in order to obtain the frequently occurring phonemes. Descriptive statistics was applied for the same. Results revealed that phonemes /n, a, e, f, h, k/ were the most frequently occurring phonemesin Hindi. Aspirated phonemes (/gh/, /ʈh/, /ph/, /ɖh/) were the least present phonemes in the data. High and front vowels were more frequently present in spoken Hindi. Considering the manner of articulation, nasals and stops had higher occurrence. Alveolar dominated considering the place of articulation of phonemes. The applications of the study are extensive and can be utilized efficiently in a variety of disciplines.